Identification of Mycoplasma pneumoniae proteins interacting with NOD2 and their role in macrophage inflammatory response - Wang, Yongyu; Ma, Chunji; Hao, Xiujing; Wang, Weili; Luo, Haixia; Li, Min (Frontiers in Microbiology, 2024)
Mycoplasma pneumoniae (M. pneumoniae, Mp) is a cell wall-deficient microorganism known to cause chronic respiratory infections in both children and adults. Nucleotide-binding oligomerization domain-containing protein 2 (NOD2) is an intracellular pattern recognition receptor primarily responsible for identifying muramyl dipeptide (MDP) found in bacterial cell walls. Previous experiments have demonstrated that Mycoplasma ovipneumoniae induces macrophage autophagy through NOD2. In this study, we conducted RNA-seq analysis on macrophages infected with M. pneumoniae and observed an up-regulation in the expression of genes associated with the NOD2 signaling pathway. Mechanistic investigations further revealed the involvement of the NOD2 signaling pathway in the inflammatory response of macrophages activated by M. pneumoniae. We utilized GST pull-down technology in conjunction with liquid chromatography-tandem mass spectrometry (LC-MS/MS) to pinpoint the M. pneumoniae proteins that interact with NOD2. Additionally, co-immunoprecipitation (Co-IP) and immunofluorescence co-localization techniques were used to confirm the interaction between DUF16 protein and NOD2. We found that DUF16 protein can enter macrophages and induce macrophage inflammatory response through the NOD2/RIP2/NF-κB pathway. Notably, the region spanning amino acids 13-90 was identified as a critical region necessary for DUF16-induced inflammation. This research not only broadens our comprehension of the recognition process of the intracellular receptor NOD2, but also deepens our understanding of the development of M. pneumoniae infection.